Clinical effectiveness and safety of low cost versus innovator brand amlodipine in hypertension: A single-blinded, randomized, crossover, noninferiority trial - Das, Alak Kumar (Indian J Pharmacol, 2016)
OBJECTIVES: A single-blinded, randomized, crossover, noninferiority trial was conducted to evaluate clinical effectiveness and safety of low-cost brand (LCB) versus innovator brand (IB) amlodipine in essential hypertension. MATERIALS AND METHODS: The primary end-point was change of systolic blood pressure (BP) from baseline to study end. Adult patients with Stage 1 hypertension or isolated systolic hypertension were randomized to receive 5 mg amlodipine LCB or IB once daily for 6 weeks in each period in a 2 × 2 crossover manner with three follow-up visits in each sequence. In 28 evaluable patients, the reduction of systolic BP (SBP), diastolic BP, and safety profile between two brands was comparable. RESULTS: The lower bound of the 95% confidence interval of the difference in reduction of SBP (−5.04 mmHg) was within the noninferiority margin of 10 mmHg. CONCLUSION: LCB amlodipine is noninferior to IB in terms of BP reduction and is a cost-effective alternative as it is less expensive than IB.